A rhodium(III) complex of the linear diborazine H3B·NMe2BH2·NMe2H: an intermediate in the dehydrocoupling of H3B·NMe2H. - Chaplin, AB; Weller, A (2011)
The solid-state structure of the rhodium complex (dimethylamine-dimethylaminoborane-borane-κ(2)H,H')dihydridobis(triisopropylphosphane-κP)rhodium(III) tetrakis[3,5-bis(trifluoromethyl)phenyl]borate, [RhH(2)(C(4)H(18)B(2)N(2))(C(9)H(21)P)(2)](C(32)H(12)BF(24)), is reported. The complex contains the linear diborazine H(3)B·NMe(2)BH(2)·NMe(2)H, a kinetically important intermediate in the transition-metal-mediated dehydrocoupling of H(3)B·NMe(2)H, ultimately affording the dimeric amino-borane [H(2)BNMe(2)](2). The structure of the title complex contains a distorted octahedral Rh(III) centre, with mutually trans phosphane ligands and cis hydride ligands. The diborazine is bound through two Rh-H-B σ-bonds and exhibits a gauche conformation with respect to the B-N-B-N backbone.